Increased serum leptin levels are associated with metabolic syndrome and carotid intima media thickness in premenopausal systemic lupus erythematosus patients without clinical atherosclerotic vascular events. (August 2018) - Demir, S; Erten, G; Artım-Esen, B; Şahinkaya, Y; Pehlivan, Ö; Alpay-Kanıtez, N; Deniz, G; Inanç, M
Aim: To assess subclinical atherosclerosis and the role of inflammatory mediators, vascular endothelial cell activation markers and adipocytokines in systemic lupus erythematosus (SLE) in the presence or absence of metabolic syndrome (MetS). Methods: We studied 66 premenopausal female SLE patients (20 with MetS) and 28 female healthy controls (HCs) without history of cardiovascular disease (CVD). Subclinical atherosclerosis was screened by measuring carotid intima media thickness (CIMT). Serum levels of high sensitivity C-reactive protein (hs-CRP), tumour necrosis factor α (TNFα), interleukin 6 (IL-6), soluble intercellular adhesion molecule 1 (sICAM-1), soluble E-selectin, leptin and visfatin were measured. Results: The mean age of MetS + SLE, MetS - and HC were 38.3 ± 6.7, 32.7 ± 9.3 and 29.9 ± 5.6 years, respectively. The mean disease duration, SLICC (Systemic Lupus International Collaborating Clinics damage index) and Systemic Lupus Erythematosus Disease Activity Index scores were 74.8 ± 54.9 months, 0.16 ± 0.48 and 1.18 ± 1.5, respectively, and were similar between MetS + and MetS - SLE patients. CIMT values were higher in both MetS + and MetS - SLE patients than HCs ( p < 0.001). sICAM-1 and erythrocyte sedimentation rate levels were higher in both MetS + and MetS - SLE patients than HCs ( p < 0.001; p = 0.002, p = 0.001). The SLE MetS + group had higher CIMT values than SLE MetS - (right: p = 0.003; left: p = 0.025). Leptin levels and homeostatic model assessment (HOMA) scores were significantly higher in SLE MetS + than SLE MetS - ( p = 0.018; p = 0.04). Leptin and CRP levels and body mass index, SLICC and HOMA scores were correlated with CIMT values (right: p = 0.03, p < 0.001, p < 0.001, p = 0.026 and p < 0.001, and left: p = 0.028, p = 0.03, p = 0.003, p = 0.002 and p = 0.025). Conclusions: In premenopausal women with SLE without a history of CVD, CIMT values were increased and related to MetS. Leptin was increased in patients with MetS and correlated with CIMT values.